Drama, Music and Media in Heritage Language Learning - Charalambous, Chryso; Yerosimou, Maria (Journal of Education Culture and Society, 2020)
This paper discusses the role that drama, music and media can play in heritage language learning. The authors will present findings from a project that took place in a community Greek school in London and explore how creative approaches can enhance students' heritage language learning, by bringing together different disciplines as well as different environments such as school, home and community. The project was part of Critical Connections: Multilingual Digital Storytelling Project, a collaboration between Goldsmiths, University of London and different community and mainstream schools in four countries.